PENGARUH BOBOT TELUR TERHADAP FERTILITAS, SUSUT TETAS, DAYA TETAS, DAN BOBOT TETAS TELUR KALKUN - Febri Ahyodi; Khaira Nova; Tintin Kurtini (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
Breeding is an effort to produce poultry breeds. To increase the qualified turkey breeds, itneeds to do firm selection to the turkey hatched eggs before hatching. The egg weight is the factorwhich influence the qualified turkey breeds. This study aimed to determine the comparison of eggweight on the fertility, weight loss, hatchability, and hatched weight of turkeys. This study washeld during a month on 1 March – 5 April 2013, located in Sukoharjo 1 Village, SukoharjoDistrict, Pringsewu Regency. The eggs used in this study were 30 turkey eggs for each treatment.The treatments consisted of egg weight T1 (70,00–74,99 g) and T2 (75,00–80,00 g). The eggstaken from 10 cages of turkey mother, three eggs from each cage. Data obtained from this studywas analyzed by using T-student Test with significant value. The result of this study showed thatthe comparison of turkey eggs weight of 70,00–74,99 g and 75,00–80,00 g were not significantlydifferent (P>0,05) on the fertility, weight loss, and hatchability. However, those weights weresignificantly different (P<0,05) on the hatched weight of turkeys.